2021
DOI: 10.5194/ms-12-237-2021
|View full text |Cite
|
Sign up to set email alerts
|

Design and control of the belt-polishing tool system for the blisk finishing process

Abstract: Abstract. According to the structural characteristics of the blisk, a new adaptive belt tool system for blisk finishing is developed. The pneumatic servo system, which is composed of the cylinder, the servo valve, and the force sensor, is used to control the polishing force. Due to the strong nonlinearity of the pneumatic system, a two-dimensional fuzzy proportion, integral, derivative (PID) controller is developed for the pneumatic force control. The proposed controller adjusts the proportional, integral, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…where α 1 and α 2 are two control gains, while z 3 /b 1 represents the compensation for the system (15) nonlinearity.…”
Section: Nonlinear Error-state Feedback Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…where α 1 and α 2 are two control gains, while z 3 /b 1 represents the compensation for the system (15) nonlinearity.…”
Section: Nonlinear Error-state Feedback Controllermentioning
confidence: 99%
“…The improved fuzzy PID controller is applied to constant-force polishing, utilizing a fuzzylogic strategy to approximate the nonlinearity of the pneumatic system. Moreover, the fuzzy PID strategy, not which does not rely on a model, addresses the issue of model uncertainty [15,16]. An intelligent PID controller, generated through the combination of the Fictitious Reference Iterative Tuning method and the Model-Free Adaptive Control method, avoids the difficulty of obtaining precise models through a data-driven approach [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to control the contact force between the end-effector and the workpiece. Researchers have conducted a large number of studies on the control of grinding robot manpower, and found that there is a large interaction force between the end-effector and the workpiece during grinding, and that the control accuracy of this force will directly affect the machining accuracy [ 20 , 21 , 22 , 23 ] and the position control of the robot. Therefore, the simultaneous control of position and force is a challenge for grinding operations [ 24 ].…”
Section: Development History Of Grinding Processmentioning
confidence: 99%
“…Therefore, it is crucial to develop an effective control method for pneumatic systems to achieve precise automatic polishing. Proportion-al-Integral-Derivative (PID) control is a widely employed method in the industrial field due to its simplicity and robustness [5,9]. PID control has been successfully implemented in various polishing applications, such as robotic belt grinding and robotic abrasive flow machining.…”
Section: Introductionmentioning
confidence: 99%